Aspectos do comportamento alimentar infantil em crianças de 0 a 10 anos: uma revisão integrativa - OLIVEIRA, Natasha Assunção (2023)
Childhood is an essential phase in the formation of eating habits and eating behavior of an adult individual, and the construction of children's eating behavior can positively or negatively influence the child's health. Thus, in this literature review, the objective was to survey aspects of children's eating behavior in children aged 0 to 10 years. The review used the following databases: MEDLINE, LILACS, BDENF, BBO, Coleciona SUS and SCIELO, and was developed in six stages: 1. elaboration of the research question, 2. definition of the sources for the selection of primary studies and the criteria for inclusion and exclusion, 3. definition and extraction of data, 4. evaluation of included studies, 5. critical analysis of the results, 6. presentation of the synthesis of the evidence found. Twelve studies were selected, which showed that the eating behavior of parents and guardians influenced children's food choices, and reward strategies had negative effects on eating habits and behavior. Regarding the school environment, there was a high consumption of processed and ultra- processed foods and a low consumption of in-natura foods, however, the benefits of nutritional education and the role of parents and caregivers in building healthy eating habits and in the development physical and mental